Theorising Childhood Citizenship, Rights and Participation (Studies in Childhood and Youth, 2018)
Focusing on children's citizenship, participation and rights, this edited collection draws on the work of a number of leading scholars in the sociology of childhood. The contributors explore a range of themes including: tensions between pragmatism and grand theory; revisiting agency/structure debates in the light of children; the challenging of binary thought prevalent in studies around 'generations' and other aspects of sociology; the manifestation of power in time and space; the application of theories into the 'real' world through NGOs, practitioners, policy makers, politicians and empirical research. The collection will be of interest to students and scholars across a range of disciplines including childhood studies, sociology, politics and social policy, as well as policy makers and practitioners interested in the citizenship, rights and participation of children. .